Guinea Bissau - The Challenge of Restoring Budgetary Discipline : A Public Expenditure Review - World Bank (Washington, DC, 2013)
This Public Expenditure Review (PER) presents a critical view of Guinea-Bissau's nascent democratic structure, one that does not ensure a clear separation of powers, which results in the need for the judiciary to exercise its lacking independence. Restoring budgetary discipline requires a series of actions in the area of fiscal policy at the macroeconomic level, as well as measures geared towards better prioritization, and allocation of public resources. At the same time, the government needs to resume efforts initiated before the conflict of 1998/99, and take steps to reform the current public finance management system. The renewed reform agenda should focus on the budget cycle encompassing the legal framework regulating it, the way the budget is formulated, executed, controlled and accounted for, so that it can be possible to improve efficiency, transparency, and accountability in the use of public resources. The main findings include institutional weaknesses and recurrent macroeconomic imbalances; an economy heavily dependent on exports, vulnerable to seasonal supply shocks; thus, to circumvent a situation of growing financial difficulties, and institutional fragility, the public finance management system has become largely informal, with grave, undesired consequences in terms of transparency and accountability. The report focuses on institutional reforms, aimed at improving the government's revenue mobilization capacity, and strengthening budgetary discipline. Recommendations for the social sectors suggest seeking additional sources of public sector financing; strengthening regulation of the private sector in Health; reviewing the structure of the education budget; and, negotiating a more flexible use of donor funding, integrating the Poverty Reduction Strategy Paper (PRSP) process with the sectors' planning efforts. To this end, the coverage of the budget should be increased, coordination of information improved, the budget preparation process strengthened, enhancing expenditure control, through greater legislative and civil society involvement in the budget process.